WMSD in slaughterhouses and the worker's health nursing service: bibliographic review (Research, Society and Development, 2022)
Introduction: There is a large number of people who are being affected by occupational disease, especially people who develop activities in the Brazilian meatpacking sector, so work-related musculoskeletal disorders (WRMD) represent an important health problem for industrial workers, both because of the number of notifications as well as the impact on the functional and work capacity of individuals. Objective: Based on a literature review, to identify working conditions that can lead to health risks, mainly to develop WMSDs, of slaughterhouse employees in Brazil and the nursing service to these workers. Methodology: This is a narrative review of the literature, carried out over a period of ten years, between 2010 and 2020 in the electronic databases LILACS, MEDLINE and SCIELO. Results and discussions: They indicate that the most prevalent WMSDs in slaughterhouse workers are those related to the upper limbs such as: carpal tunnel syndrome, synovitis and tenosynovitis, a result of the conditions that most cause damage to the health of the worker since lifting excessive loads, inadequate postures, cold environment and repetitive movements. Conclusion: It is recommended that the occupational nurse develop skills to verify the risk factors within the work environment, since it is from them that the nurse performs safety in the workplace, as well as establishes programs to promote worker health.